Impact of Training, Education, and Physical Work Environment on Employee Productivity: Insights from the Public Works Office - Hulu, Helen Saputri; Sinaga, Irwan Nopian; Harahap, Rifqah (INSPIRETECH GLOBAL INSIGHT, 2025)
Purpose: This study investigates the impact of job training, formal education, and physical work environment on employee productivity at the Public Works Office in Lubuk Pakam, Indonesia. The research addresses critical gaps in understanding how these human resource development factors synergistically influence organizational performance in public sector institutions. Materials and Methods: A quantitative research design was employed with a saturated sampling technique involving all 75 employees at the Public Works Office in Lubuk Pakam. Data were collected using validated questionnaires with Likert scale measurements. The instruments demonstrated high reliability (Cronbach's Alpha: 0.964 for training, 0.837 for education, 0.925 for physical work environment, and 0.972 for productivity). Multiple linear regression analysis was conducted using SPSS version 27 to examine the relationships between independent variables (job training, education, physical work environment) and the dependent variable (employee productivity). Results: The regression analysis yielded the equation Y = -7.131 + 0.317X₁ + 0.505X₂ + 0.924X₃ + e. Partial t-tests revealed that job training (t = 4.262, p < 0.001), education (t = 2.831, p = 0.006), and physical work environment (t = 6.552, p < 0.001) all exerted positive and statistically significant effects on employee productivity. Simultaneous F-test (F = 216.388, p < 0.001) confirmed the collective significance of all predictors. The model explained 89.7% of variance in productivity (Adjusted R² = 0.897), indicating exceptionally strong predictive power. Conclusions: This study provides robust empirical evidence that holistic investment in employee training, educational advancement, and physical workspace optimization significantly enhances productivity in public sector organizations. The physical work environment emerged as the strongest predictor, followed by job training and education. These findings underscore the critical importance of integrated human resource development strategies for achieving optimal organizational performance in Indonesian public institutions.